Amyloid‐β activates NLRP3 inflammasomes by affecting microglial immunometabolism through the Syk‐AMPK pathway. (20th December 2022) - Jung, Eun Sun; Suh, Kyujin; Han, Jihui; Kim, Heyyoung; Kang, Hyung‐Sik; Choi, Won‐Seok; Mook‐Jung, Inhee
Abstract: Background: Neuroinflammation is considered one of major factors in the pathogenesis of Alzheimer's disease (AD). In particular, inflammasome activation, including NLRP3 inflammasome in microglia, is regarded as fundamental for the pro‐inflammatory response of immune cells (Hanslik & Ulland, 2020). Aβ functions to primarily activate microglia in AD and reports have been made that Aβ can activate NLRP3 inflammasome(Halle et al., 2008). However, the precise molecular mechanism through which the NLRP3 inflammasome is associated with AD pathologies remains unclear. Method: Primary microglia were treated with LPS and Aβ, and the induced signaling pathway were examined by RT‐PCR, western blot and immunostaining. Effect of flufenamic acid (FA) were examined and various inhibitors of Syk, AMPK and NLRP3 were used for the verification of the hypothesis. AD mouse model expressing Aβ and tau pathology were intraperitoneally treated with FA. After behavior tests, their brains were obtained for western blot and immunostaining. Result: Aβ activates the NLRP3 inflammasome in microglia by activating Syk and inhibiting AMPK. Deactivated AMPK induces metabolic dysregulation, mitochondrial fragmentation and reactive oxygen species formation, leading to the activation of the NLRP3 inflammasome. In addition, flufenamic acid (FA), a member of non‐steroid anti‐inflammatory drugs, was found to effectively inhibit activation of the microglial NLRP3 inflammasome by regulating Syk and AMPK. Importantly, FA has marked therapeutic effects on major AD pathologies including amyloid plaque formation, tau phosphorylation, gliosis and memory dysfunction in vivo in microglia‐dependent way. Conclusion: The molecular mechanism of microglial NLRP3 inflammasome activation by Aβ was demonstrated to be Syk‐AMPK pathway. Also, FA can be repurposed for inhibiting microglial activation of the NLRP3 inflammasome, which is a potential treatment for AD. *References Hanslik, K. L., & Ulland, T. K. (2020). The Role of Microglia and the Nlrp3 Inflammasome in Alzheimer's Disease. Frontiers in Neurology, 11 . Halle, A., Hornung, V., Petzold, G. C., Stewart, C. R., Monks, B. G., Reinheckel, T., Fitzgerald, K. A., Latz, E., Moore, K. J., & Golenbock, D. T. (2008). The NALP3 inflammasome is involved in the innate immune response to amyloid‐β. Nature immunology, 9 (8), 857.